English motivational discourse in the light of postmodernist tradition - Gilyasev Yu.V. (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper provides the description of particular aspects of the English motivational discourse in the light of wide-spread postmodernist aesthetics. It is aimed at explicating postmodernist mode in the motivational literature in English. The comparative analysis is based on the observation of 3 excerpts containing 3500 words in volume and each belonging to a popular science edition, a motivational paper, and a scientific report in the field of psychology. The methodological framework involves general scientific methods of analysis, synthesis, and generalization, methods of optional sampling and scoring, as well as discourse analysis based on the function and onomastic approach, contextual analysis, and comparative interpretation. The description has been performed by distinction of typological traits attributed to the postmodernist style of reality representation and finding these traits in the selected sample of the motivational paper. The mythological character of postmodernist vision is often named as its fundamental feature considered through logic and cognitive perspective. That is proven true by a larger portion of emotive vocabulary found in the analyzed excerpt in comparison with the two other samples. The narrative strategy together with story-telling as a primary means of communication, first-person statements, the focus on the personal experience and the verbalization of the addresser’s emotional reaction testify to the prevailing irrational and natural logic in his forming the world view for the reader. Language game, intertextuality, pastiche, and style syncretism are often distinguished as typological traits attributed to the postmodernist way of reality representation on the level of discourse. The findings give evidence to a moderate variation of the language forms in the analyzed sample of the motivational paper in terms of meaning and its speech representation. This language manipulation in the work took the shape of the author’s coinage, contact and rhythmical collocation of some sentences and their parts. Style syncretism is observed through co-occurrence of publicist, fictional as well as popular science style of presentment in the text. The obvious author’s biased approach to the issue marks the publicistic nature of the discourse. Intertextuality, traditionally associated with reference to precedent texts and phenomena, acquires in the motivational literature new pragmatics: all citation and referencing are involved only to enforce the author’s stand and used as means of manipulative communication as they are selected intentionally and subjectively.